2007
DOI: 10.3732/ajb.94.4.625
|View full text |Cite
|
Sign up to set email alerts
|

Does Macaronesia exist? Conflicting signal in the bryophyte and pteridophyte floras

Abstract: Macaronesia, which includes five mid-Atlantic archipelagos (Azores, Madeira, Selvagems, Canaries, and Cape Verdes), has been traditionally recognized as a distinct biogeographic unit whose circumscription has been intimately associated with the hypothesis that the flora is a relict of a formerly broadly distributed subtropical Tertiary flora. The concept of Macaronesia is revisited here using parsimony and Bayesian analyses of floristic data sets for the moss, liverwort, and pteridophyte floras. All analyses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 59 publications
5
66
0
2
Order By: Relevance
“…Many bryophyte species exhibit a striking hyper-Atlantic distribution pattern that is often disjunct between Macaronesia and the western fringe of Europe (15). Such distributions may reflect a similar history with Macaronesia serving as a refugium and a source area for the postglacial recolonization of Europe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many bryophyte species exhibit a striking hyper-Atlantic distribution pattern that is often disjunct between Macaronesia and the western fringe of Europe (15). Such distributions may reflect a similar history with Macaronesia serving as a refugium and a source area for the postglacial recolonization of Europe.…”
Section: Resultsmentioning
confidence: 99%
“…1), which form a distinct biogeographic unit referred to as Macaronesia (sensu ref. 15), we confront theoretical expectations on patterns of genetic diversity in the moss Platyhypnidium riparioides. We aim to determine whether dispersal ability of this moss erode any signature of founding events on extant patterns of genetic variation.…”
mentioning
confidence: 99%
“…We assumed that the nearest continent was the main source area for islands. This assumption is supported in Macaronesia, a biogeographical region comprised of the Azores, Canary Islands and Madeira, where the bryophyte flora exhibits closer affinities with the European flora than with any of the other floras world-wide (Vanderpoorten, Carine & Rumsey 2007). Because island species are assumed to originate from a continental ancestor, and because island taxa are expected to evolve syndromes in response to the specificities of the island environment (see Whittaker & Fern andez-Palacios 2007; for review), we further assumed that character states observed in islands are derived.…”
Section: S E L E C T I O N a N D S C O R I N G O F L I F E -H I S T Omentioning
confidence: 92%
“…We excluded the Azores, Canary Islands and Madeira (Macaronesia) because their high degree of endemism points to their development being independent from Europe (Wunderlich 1991), with more affinities to Africa (e.g., Lloris et al 1991;Vanderpoorten et al 2007). This definition corresponds to that used by the ''araneae-Spiders of Europe'' website ).…”
Section: Biogeographical Definition Of Europementioning
confidence: 99%